Autohemotherapy In The Clinical Management Of Cutaneous Papillomatosis In A Cow : A Case Report - Chandrashekar, T.; Shruthi, J. S.; Amith, N. G.; Kshama, M. A.; Pramodh, J.K.; Handage, Sushant (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Papilloma virus is a non enveloped double stranded DNA virus, epitheliotropic, host specific and cause proliferative lesions in many Mammalian and Avian species. Although infection with papilloma virus occur in many species, only those which affect cattle, horses and dogs are of clinical significance (Quinn et al . 2007). Papilloma virus usually affects basal cells of squamous epithelium. As a result of minute abrasions, they may also gain entry at the vulnerable sites such as junctions between different types of epithelia. Bovine cutaneous papillomatosis is caused by several types of bovine papilloma virus. Cutaneous fibro papillomas are generally associated with BPV types 1,2 & 5 whereas BPV type 3 or 6 are linked to papillomas in which fibrous tissue is minimal. Teat fibro papillomas associated with BPV-5 infection have smooth surface and are called rice grain type whereas those associated with BPV-6 are called frond type. Lesions are most commonly observed in young animals and regress spontaneously after weeks or months. Regression is attributed to the development of cell mediated immunity (Quinn et al. 2007) .